2019
DOI: 10.15406/acp.2019.04.00074
|View full text |Cite
|
Sign up to set email alerts
|

Efficient microorganisms with probiotic effect, an alternative in swine health

Abstract: Use of microorganisms with probiotic capacity nowadays tends to be established in different systems of animal production throughout the world. The improvement in bioproductive behaviour when using probiotics in animal production depends not only on the production stage, but also on the selection of the strains used and the method of administration. Because the demand of international markets are products (meat, milk and eggs) healthy and that these do not directly or indirectly affect the health of man when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Timmerman et al [35] showed that probiotics based on numerous strains of the same species as well as preparations composed of strains belonging to different species of microorganisms turn out to be more effective in action because they are active in many places of the intestine in relation to different target cells and show different mechanisms of action. The use of a mixture of Lactobacillus spp., Lactobacillus acidophulus, Streptococcus thermophilus, Bacillus subtilis, and Kluyveromyces fragilis L-4 uclv strains in pig nutrition reduces the occurrence of gastrointestinal diseases with symptoms of diarrhoea and has a positive effect on the production parameters [36,37]. Probiotics containing Lactobacillus spp., Bifidobacterium spp., Enterococcus spp., and Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Timmerman et al [35] showed that probiotics based on numerous strains of the same species as well as preparations composed of strains belonging to different species of microorganisms turn out to be more effective in action because they are active in many places of the intestine in relation to different target cells and show different mechanisms of action. The use of a mixture of Lactobacillus spp., Lactobacillus acidophulus, Streptococcus thermophilus, Bacillus subtilis, and Kluyveromyces fragilis L-4 uclv strains in pig nutrition reduces the occurrence of gastrointestinal diseases with symptoms of diarrhoea and has a positive effect on the production parameters [36,37]. Probiotics containing Lactobacillus spp., Bifidobacterium spp., Enterococcus spp., and Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%